225Ac-PSMA-617 for PSMA-targeted α-radiation therapy of metastatic castration-resistant prostate cancer - Kratochwil, Clemens; Giesel, Frederik L.; Haberkorn, Uwe (Journal of nuclear medicine, 2016)
Prostate-specific membrane antigen (PSMA) is a promising target in prostate cancer. Recently, we started the first-in-human treatment with an α-radionuclide-labeled PSMA ligand. Although the case series is still ongoing, we here report in advance about two patients in highly challenging clinical situations who showed a complete response to 225Ac-PSMA-617 therapy. Methods: 68Ga-PSMA-11 PET/CT validated the presence of the PSMA-positive tumor phenotype. A 100-kBq activity of 225Ac-PSMA-617 per kilogram of body weight was administered bimonthly. Prostate-specific antigen response and hematologic toxicity were measured at least every 4 wk. Restaging was performed with 68Ga-PSMA-11 PET/CT. Results: Both patients experienced a prostate-specific antigen decline to below the measurable level and showed a complete response on imaging. No relevant hematologic toxicity was observed. Xerostomia was the only mentionable clinical side effect. Conclusion: Targeted α-therapy with 225Ac-PSMA-617, although still experimental, obviously has strong potential to significantly benefit advanced-stage prostate cancer patients.